Identification and functional analysis of three new anthocyanin R2R3‐MYB genes in Petunia - Zhang, Hechen (John Wiley and Sons Inc., 2019)

(untitled) (Plant Direct)
We identified three novel members of the R2R3‐MYB clade of anthocyanin regulators in the genome of the purple flowering Petunia inflata S6 wild accession, and we called them ANTHOCYANIN SYNTHESIS REGULATOR (ASR). Two of these genes, ASR1 and ASR2, are inactivated by two different single base mutations in their coding sequence. All three of these genes are absent in the white flowering species P. axillaris N and P. parodii, in the red flowering P. exserta, and in several Petunia hybrida lines, including R27 and W115. P. violacea and other P. hybrida lines (M1, V30, and W59) instead harbor functional copies of the ASR genes. Comparative, functional and phylogenic analysis of anthocyanin R2R3‐MYB genes strongly suggest that the ASR genes cluster is a duplication of the genomic fragment containing the other three R2R3‐MYB genes with roles in pigmentation that were previously defined, the ANTHOCYANIN4‐DEEP PURPLE‐PURPLE HAZE (AN4‐DPL‐PHZ) cluster. An investigation of the genomic fragments containing anthocyanin MYBs in different Petunia accessions reveals that massive rearrangements have taken place, resulting in large differences in the regions surrounding these genes, even in closely related species. Yeast two‐hybrid assays showed that the ASR proteins can participate in the WMBW (WRKY, MYB, B‐HLH, and WDR) anthocyanin regulatory complex by interacting with the transcription factors AN1 and AN11. All three ASRs can induce anthocyanin synthesis when ectopically expressed in P. hybrida lines, but ASR1 appeared to be the most effective. The expression patterns of ASR1 and ASR2 cover several different petunia tissues with higher expression at early stages of bud development. In contrast, ASR3 is only weakly expressed in the stigma, ovary, and anther filaments. The characterization of these novel ASR MYB genes completes the picture of the MYB members of the petunia anthocyanin regulatory MBW complex and suggests possible mechanisms of the diversification of pigmentation patterns during plant evolution.